Seaweeds as source of the essential elements - Caroline Rodrigues Albuquerque; Vera Akiko Maihara; Cassio Bessa De Lima; Paulo Sergio Cardoso Silva (Brazilian Journal of Radiation Sciences)
Overtime seaweeds have been used as a food mainly due to their high nutritional value. This type of food is considered as functional food and contributes to the nutritional human requirements, being beneficial to human health. In this study 13 edible seaweed samples acquired in the marked of São Paulo city were analyzed and the concentrations of elements Cl, K, Mg, Mn and Na were determined by Instrumental Neutron Activation Analysis (INAA). The following edible seaweeds were analyzed: Nori (Porphyra umbilicates); Hijiki (Hijikia fusiforme); Kombu (Laminaria sp.) and Wakame (Undaria pinnatifida) species from China, USA, Japan and South Korea. The Undaria pinnatifida species presented the highest Na concentration and the lowest K level. The highest variation was obtained for Mn in the Porphyra umbilicates species.